Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa - Nurul Husda; Sriyanti Mustafa; Vernita Sari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This study aims to determine the effect of learning independence on mathematics learning achievement of students of class X UPT SMA NegeriI 1 Parepare, while this type of research is a quantitative research using the Ex Post Facto approach. The population in this study were students of class X which consisted of 6 classes. The sample in this study was class X IPA 6 which amounted to 36 people, selected using a sampling technique called Cluster Random Sampling. The data of this research were obtained by using research instruments in the form of a learning independence questionnaire and documentation of learning achievement in the form of the odd semester report cards for the academic year 2021/2022. The data collection techniques used were questionnaire techniques and documentation techniques.The result of the descriptive analysis obtained an average score of 72.50 for learning independence and a standart deviation of 7.99. Students’ mathematics learning achievement is in the very high category with an average score of 85.44 and a standard deviation of 4.11. The results of the inferential analysis showed that there was a positive effect of learning independence on mathematics learning achievement of class X students of UPT SMA Negeri 1 Parepare with a significant value of 0.038 < 0.05.